High-throughput phagocytosis assay utilizing a pH-sensitive fluorescent dye. (December 2005) - Beletskii, Anton; Cooper, Michael; Sriraman, Priya; Chiriac, Camelia; Zhao, Lihong; Abbot, Stewart; Yu, Liming
We describe a development of a novel high-throughput phagocytosis assay based on a pH-sensitive cyanine dye, CypHer5E™, which is maximally fluorescent in an acidic environment. This dye is ideally suited for the study of phagocytosis because of the acidic conditions generated in the intracellular phagocytic vesicles after particle uptake. Use of CypHer5E-labeled particles results in greatly reduced background from noninternalized particles and makes the assay more robust. Additionally, CypHer5E-labeled particles are resistant to fluorescence quenching observed in the aggressive and acidic environment of the phagosome with traditional dyes. The CypHer5E-based assay has been shown to work reliably in a variety of cell types, including primary human monocytes, primary human dendritic cells, primary human endothelial cells, human monocytic THP-1 cell line, and human/mouse hybrid macrophage cell line WBC264-9C. Inhibition of CypHer5E bead uptake by cytochalasin D was studied, and the 50% inhibition concentration (IC50 ) was determined. The assay was performed in 96- and 384-well formats, and it is appropriate for high-throughput cellular screening of processes and compounds affecting phagocytosis. The CypHer5E phagocytosis assay is superior to existing protocols because it allows easy distinction of true phagocytosis from particle adherence and can be used in microscopy-based measurement of phagocytosis.